GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 244 species occurrences available in GBIF matching the query: TaxonKey: Blepharida rhois (Forster, 1771). The dataset includes 244 records from 12 constituent datasets: 1 records from Lund Museum of Zoology - Insect collections (MZLU). 7 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 6 records from Museum of Comparative Zoology, Harvard University. 8 records from iNaturalist Research-grade Observations. 46 records from Recent Invertebrates Specimens. 3 records from Biodiversidad de coleópteros y arañas de las Sierras de Taxco-Huautla. 82 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 10 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 5 records from Museum of Southwestern Biology, Division of Arthropods. 5 records from Snow Entomological Museum Collection. 67 records from UCMC_Entomology. 4 records from Insect Occurrence Data from MIZA. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences